Combined immunophenotyping and FISH identifies the involvement of B-cells in 5q- syndrome. - Jaju, R; Jones, M; Boultwood, J; Kelly, S; Mason, D; Wainscoat, J; Kearney, L (2000)
The 5q- syndrome is a distinct subtype of myelodysplastic syndrome (MDS) characterized by refractory anemia, deletion of the long arm of chromosome 5, del(5q), as the sole cytogenetic abnormality, and a low frequency of transformation to acute leukemia. Using combined immunophenotyping and fluorescence in situ hybridization (FISH), studies were carried out on bone marrow smears of three 5q- syndrome cases to identify the cell lineages carrying the 5q deletion. In all three cases, the granulocytic, monocytic, and erythroid lineages possessed the del(5q) clonal marker, whereas the T-lymphocytes did not. Interestingly, in one case, cells of B-lymphoid lineage also showed the presence of the del(5q). This is the first report to date showing involvement of an acquired 5q deletion associated with MDS in B-cells. This result suggests that in some cases, MDS arises in a multipotent cell with a capacity to differentiate into both myeloid and lymphoid cells.